New Roadmaps for Non-muscle-invasive Bladder Cancer With Unfavorable Prognosis - Pane, Katia; Mirabelli, Peppino; Coppola, Luigi; Illiano, Ester; Salvatore, Marco; Franzese, Monica (Frontiers in Chemistry, 2020)
About 70 % of bladder cancer are diagnosed as non-muscle-invasive bladder cancers (NMIBCs) whilst the remaining are muscle-invasive (MIBCs). The European Association of Urology (EAU) guidelines stratify NMIBCs into low-, intermediate-, and high-risk for treatment options. NMIBCs low-risk undergo only the transurethral resection of the bladder (TURB), whereas for NMIBCs intermediate-, and high-risk, the transurethral resection of the bladder (TURB) with or without Bacillus Calmette-Guérin (BCG) immune or chemotherapy are the standard treatments. A minority of NMIBCs, show unfavorable prognosis. High-risk NMIBCs have a high rate of disease recurrence and/or progression to muscle-invasive tumor and BCG treatment failure. The heterogeneous nature of NMIBCs poses challenges for clinical decision-making. In 2020, EAU made some changes to NMIBCs BCG failure definitions and treatment options, highlighting the need for reliable molecular markers for improving the predictive accuracy of currently available risk tables. Nowadays, next-generation sequencing (NGS) has revolutionized the study of cancer biology, providing diagnostic, prognostic, and therapy response biomarkers in support to precision medicine. Integration of NGS with other cutting-edge technologies might help to decipher also bladder tumor surrounding aspects such as immune system, stromal component, microbiome, and urobiome; altogether this might impact the clinical outcomes of NMBICs especially in the BCG responsiveness. This review focuses on NMIBCs with unfavorable prognoses providing molecular prognostic factors from tumor immune and stromal cells, and the perspective of urobiome and microbiome profiling on therapy response. We provide information on the cornerstone of immunotherapy and new promising bladder-preserving treatments and ongoing clinical trials for BCG unresponsive.